2019
DOI: 10.1177/1545968319832606
|View full text |Cite
|
Sign up to set email alerts
|

Is Unilateral Spatial Neglect Associated With Motor Recovery of the Affected Upper Extremity Poststroke? A Systematic Review

Abstract: Background and Purpose. Individuals with stroke often present symptoms of multiple domains, such as weakness of the affected upper extremity (UE) and unilateral spatial neglect (USN), which are both associated with poor functional outcome. The aims of this systematic review were to search and review studies that investigated (1) the relationship between USN and affected UE sensorimotor recovery poststroke and (2) the effectiveness of sensorimotor interventions to improve the affected UE in patients with USN. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…We found that length of hospital stay was more than double in individuals with spatial neglect and neglect was associated with much greater dependency at discharge and death. This is in line with previous reports of the poor longer term outcome of stroke survivors with neglect [13]. People with neglect were more likely to be discharged to a care home, probably an indication of their increased dependency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that length of hospital stay was more than double in individuals with spatial neglect and neglect was associated with much greater dependency at discharge and death. This is in line with previous reports of the poor longer term outcome of stroke survivors with neglect [13]. People with neglect were more likely to be discharged to a care home, probably an indication of their increased dependency.…”
Section: Discussionsupporting
confidence: 92%
“…Critically for rehabilitation, many neglect patients present with anosognosia and deny difficulties with perception or control of movement, being not aware that they are experiencing these symptoms [6,7]. Therefore, it is not surprising that neglect early after stroke [8,9], as well as enduring neglect [10][11][12], is a prognostic indicator for reduced functional independence following stroke [13]. This is further impacted by the association of neglect with more severe sensory impairment [14] which is in itself a prognostic indicator of poorer recovery after stroke [15].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of inconsistent assessment of UN has previously been identified and is echoed in the results of this review [15,22]. At present, there is only a single assessment tool that covers all three hemi-spaces, the CBS.…”
Section: Assessment Of Unmentioning
confidence: 70%
“…Reviews of UN report an association with poor motor recovery after stroke [22][23][24]. A critical contributor to the ability to control movement during functional tasks is proprioception [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation